The Effect of Technical Role Playing Group Guidance Services on The Learning Fatigue of Vocational School Students - Putri, Vidia Windandari; Syaimi, Khairina Ulfa; Saragih, Nurul Azmi; Hutasuhut, Dina Hidayati (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Various factors, both internal and external, can influence student learning fatigue. Consequently, the necessity for an efficacious strategy to surmount this predicament is paramount. A potential approach entails the utilization of group counselling services, incorporating role-playing techniques. The present study was conducted with the objective of ascertaining the impact of role-playing group counselling services on the learning fatigue of students at vocational school 07 Medan. The findings of the study, which have been thoroughly analyzed, have indicated that the results of the hypothesis test, which was conducted using the paired sample t-test, demonstrate a significant effect of the service in reducing student learning fatigue. The calculated t-value is greater than the table t-value (7.592 > 2.262), indicating that the relationship between the two variables is positive. The significance value of 0.000 is less than the significance level of 0.05 (0.000 < 0.05), indicating that the research hypothesis is accepted. Group counseling services utilizing role-playing techniques have demonstrated efficacy in mitigating student learning fatigue. The implementation of role-playing activities has been demonstrated to have a number of beneficial effects on the learning environment.